2017
DOI: 10.1371/journal.pone.0175518
|View full text |Cite
|
Sign up to set email alerts
|

Serine protease Bm-SP142 was differentially expressed in resistant and susceptible Bombyx mori strains, involving in the defence response to viral infection

Abstract: Bm-SP142 is a 35 kDa protease in the silkworm, but its exact functions remain unknown. In this study, sequence alignment revealed that the His-Asp-Ser catalytic triad is embedded in the sequence motif, establishing Bm-SP142 as a serine protease. Soluble recombinant GST-BmSP142 was expressed and purified, and serine protease activity was confirmed in vitro. RT-qPCR results indicated that Bm-SP142 was mainly expressed in the middle part of the silkworm midgut, and Bm-SP142 transcripts were significantly up-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…Many digestive-related proteases are only expressed in the midgut or are highly expressed in the midgut. For example, the serine proteases (SP), a major class of digestive proteases accounting for 95% of digestive activity in Lepidoptera, showed similar expression profiles to that of BmLHA in the B. mori [39][40][41][42]. While the BmLHA expressed at lower levels in the Malpighian tube and other tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many digestive-related proteases are only expressed in the midgut or are highly expressed in the midgut. For example, the serine proteases (SP), a major class of digestive proteases accounting for 95% of digestive activity in Lepidoptera, showed similar expression profiles to that of BmLHA in the B. mori [39][40][41][42]. While the BmLHA expressed at lower levels in the Malpighian tube and other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the expression level of BmLHA was higher in the first day of fifth instar compared to the fourth day of fourth instar prior to the moulting stage, and demonstrated very low expression during the moulting stage. Liu et al [40] found that the expression level of BmSP36 was regulated by juvenile hormone (JH), with the same expression profiles in different moulting stages. At the same time, Zhang et al [27] demonstrated that B. mori pancreatic lipase-like gene (BmPLLG) is involved in pheromone biosynthesis via activation of neuropeptide (PBAN)-induced sex pheromone biosynthesis and released by influencing bombykol production.…”
Section: Discussionmentioning
confidence: 99%
“…Insights into the atomic level of SerPs structure–function link reveal the significance of the catalytic Ser motions [ 201 , 202 ]. Notably, an evolutionarily conserved catalytic domain Ser–His–Asp contains Ser residue [ 203 , 204 ] providing sensitivity to the AAs racemization. It is in the agreement with a well-known fact that incorporation D-AAs into peptide chain diminishes their susceptibility to proteases [ 205 ].…”
Section: Chirality At Protein Level: Role In Ptmsmentioning
confidence: 99%
“…Nakazawa and Ponnuvel [9,10] previously reported that alkaline trypsin and SP-2 purified from the digestive juice of B. mori larvae had strong antiviral activity against BmNPV under in vitro conditions. Bm-SP142 could effectively impair the ability of the virus to infect BmN cells and silkworms, and overexpression of Bm-SP142 could inhibit viral propagation in BmN cells [40]. Additionally, Chen et al [41] found that the some anti-BmNPV genes expressed significantly higher in the resistant strains compared to susceptible strains.…”
Section: Enzymes Response To Bmnpv Infection In Different Resistant Smentioning
confidence: 99%